1995
DOI: 10.1159/000244173
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Transport and Processing of Immunoglobulin G in the Neonatal and Adult Rat

Abstract: The proximal intestine of neonatal rats expresses a specific receptor (RFcn) that binds immunoglobulin G (IgG) and is no longer expressed after weaning. The aim of this study was to quantify and compare the intestinal transport and processing of IgG in intestinal fragments with or without RFcn, with the fluid-phase transport of horseradish peroxidase (HRP). The mucosal to serosal transport and degradation of IgG and HRP were measured in neonatal and adult rats in vitro in Ussing chambers. IgG transcytosis occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 17 publications
2
27
1
Order By: Relevance
“…It is interesting to note that the literature already has a number of studies that demonstrate transcytosis of intact proteins across intestinal epithelial cells (36 -40), and in some cases the studies report rates of transcytosis (29,(41)(42)(43). The rate of transcytosis of BoNT/A determined in the present study is within the range of that reported for other proteins, but it is at the low end of the range.…”
Section: Discussionsupporting
confidence: 78%
“…It is interesting to note that the literature already has a number of studies that demonstrate transcytosis of intact proteins across intestinal epithelial cells (36 -40), and in some cases the studies report rates of transcytosis (29,(41)(42)(43). The rate of transcytosis of BoNT/A determined in the present study is within the range of that reported for other proteins, but it is at the low end of the range.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast to the rat and mouse neonatal intestine, where maternal IgG binds FcRn at the apical cell surface (47), FcRn expressed in the rat yolk sac appears to bind IgG only within apical compartments after fluidphase uptake (48). Also, Benlounes et al (49) have observed transepithelial IgG transport across isolated neonatal rat intestine in which both the serosal and mucosal solutions were clamped at neutral pH and thus inhibitory for IgG binding to FcRn at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments were done using intestinal samples from neonatal rats that had been fed Au-Fc. The concentration of Au-Fc that was fed to neonatal rats was 2-3 μM, approximately equal to the IgG concentration in rat milk, because higher concentrations saturate FcRn, resulting in degradation of excess IgG (Benlounes et al, 1995). In this system for Au-Fc uptake, we had two controls for the specificity of uptake and gold enhancement: first, the presence or absence of ingested Au-Fc, and second, the requirement that enhanced gold particles should appear in physiologically-relevant locations in cells; e.g., in locations corresponding to FcRn expression (apical cell surface, coated vesicles and tubulovesicular compartments) in samples from the proximal small intestine, and inside degradative compartments (e.g., giant lysosomes) in samples from the neonatal distal small intestine (ileum), which does not express FcRn (Rodewald, 1973).…”
Section: Specific Enhancement Of Endocytosed 14 Nm Au-fc In Chemicalmentioning
confidence: 99%